Magnetic Resonance Angiography Principles and Applications - Carr, James C.; Carroll, Timothy J.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
Magnetic Resonance Angiography: Principles and Applications is a comprehensive text covering magnetic resonance angiography (MRA) in current clinical use. The first part of the book focuses on techniques, with chapters on contrast-enhanced MRA, time of flight, phase contrast, time-resolved angiography, and coronary MRA, as well as several chapters devoted to new non-contrast MRA techniques. Additionally, chapters describe in detail specific topics such as high-field MRA, susceptibility-weighted imaging, acceleration strategies such as parallel imaging, vessel wall imaging, targeted contrast agents, and low dose contrast-enhanced MRA. The second part of the book covers clinical applications of MRA, with each chapter describing the MRA techniques and protocols for a particular disease and vascular territory, as well as the pathology and imaging findings relevant to the disease state being discussed. Magnetic Resonance Angiography: Principles and Applications is designed to bring together into a single textbook all of the MRA techniques in clinical practice today and will be a valuable resource for practicing radiologists and other physicians involved in the diagnosis and treatment of vascular diseases, as well as biomedical physicists, MRI technologists, residents, and fellows. Editors James C. Carr, MD, is Director of Cardiovascular Imaging and Associate Professor of Radiology and Medicine at Northwestern University Feinberg School of Medicine, Chicago, Illinois, USA. Timothy J. Carroll, PhD, is Assistant Professor in the Department of Radiology at Northwestern University Feinberg School of Medicine, Chicago, Illinois, USA.
Keywords: Medicine; Radiology, Medical; Cardiology; Vascular Surgery; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Cardiology; Vascular Surgery